DNA methylation functions as a critical regulator of Kir4.1 expression during CNS development. Issue 3 (10th January 2014) - Nwaobi, Sinifunanya E.; Lin, Erica; Peramsetty, Sasank R.; Olsen, Michelle L.
<x xml:space="preserve">Abstract</x> Kir4.1, a glial‐specific K+ channel, is critical for normal CNS development. Studies using both global and glial‐specific knockout of Kir4.1 reveal abnormal CNS development with the loss of the channel. Specifically, Kir4.1 knockout animals are characterized by ataxia, severe hypomyelination, and early postnatal death. Additionally, Kir4.1 has emerged as a key player in several CNS diseases. Notably, decreased Kir4.1 protein expression occurs in several human CNS pathologies including CNS ischemic injury, spinal cord injury, epilepsy, ALS, and Alzheimer's disease. Despite the emerging significance of Kir4.1 in normal and pathological conditions, its mechanisms of regulation are unknown. Here, we report the first epigenetic regulation of a K+ channel in the CNS. Robust developmental upregulation of Kir4.1 expression in rats is coincident with reductions in DNA methylation of the Kir4.1 gene, KCNJ10. Chromatin immunoprecipitation reveals a dynamic interaction between KCNJ10 and DNA methyltransferase 1 during development. Finally, demethylation of the KCNJ10 promoter is necessary for transcription. These findings indicate DNA methylation is a key regulator of Kir4.1 transcription. Given the essential role of Kir4.1 in normal CNS development, understanding the regulation of this K+ channel is critical to understanding normal glial biology. GLIA 2014;62:411–427